DIGITAL SERVICES: THEIR ATTRIBUTES AND INTERCONNECTION WITH THE ARCHITECTURE OF THE ENTERPRISE - E. Zaramenskikh (Вестник университета, 2018)
Digital services as an independent product of information activity that facilitates the implementation of business processes, presents their attributes, and explores the possibilities of composing digital services and elements of the enterprise architecture have considered. The author came to conclusion, that the transition to the digital economy and the formation of digital services require clarification and rethinking of management approaches, in terms of rethinking the structure of the enterprise on a fundamentally new level, namely as a set of services located at different levels of management.